Unlocking Student Creativity and Research Potential in Bangladesh: The Crucial Role of Policy Makers in Breaking Deadlocks - Md. Alomgir Hossan; Md Amirul Islam; Murshida Khatun (MultiTech Publisher, 2023)
There are 53 public universities in Bangladesh, University of Rajshahi is a significant one of them. This study focuses on the student’s present condition of creativity and research potential. The researchers in this paper tried to find out the causes of why students are not interested in research, especially in the Social Science and Arts Faculties including an out-of-date curriculum, a dearth of resources, and limited access to technology, Bangladesh's existing educational system frequently stifles students' creativity and restricts their ability to conduct research. This research paper has developed a mixed methodology to collect data and analysis. From 10 departments (856 postgraduate students) 265 respondents take part in this research. Collecting the data, we analyzed them and find out effective ways how the students can cope with the existing problem. Finally, we discuss the role of policymakers including policymakers should give priority to measures upgrading curricula to foster creativity, increasing funding for research and innovation, and allocating money to infrastructure and technology to improve access to information and communication.